Finance and the Earth system – Exploring the links between financial actors and non-linear changes in the climate system. (November 2018) - Galaz, Victor; Crona, Beatrice; Dauriach, Alice; Scholtens, Bert; Steffen, Will
Highlights: Financial capital plays a key role in economic activities around the world, as well as in efforts to avoid climate change. We develop a methodology that link financial actors to industries modifying tipping elements in Earth's climate system. We identify "Financial Giants" who through their ownership have considerable influence over climate stability. We assess the incentives of "Financial Giants" to collaborate and use their influence to help stabilize tipping elements. Abstract: Financial actors and capital play a key role in extractive economic activities around the world, as well as in current efforts to avoid dangerous climate change. Here, in contrast to standard approaches in finance, sustainability and climate change, we elaborate in what ways financial actors affect key biomes around the world, and through this known "tipping elements" in the Earth system. We combine Earth system and sustainability sciences with corporate finance to develop a methodology that allows us to link financial actors to economic activities modifying biomes of key importance for stabilizing Earth's climate system. Our analysis of key owners of companies operating in the Amazon rainforest (Brazil) and boreal forests (Russia and Canada) identifies a small set of international financial actors with considerable, but as of yet unrealized, globally spanning influence. We denote these "Financial Giants", and elaborate how incentives and disincentives currently influence their potential to bolster or undermine the stability of the Earth's climate system.